Peran Guru dalam Menangani Kesulitan Belajar Matematika pada Siswa dengan Diskalkulia di SLB Yasmin Sumenep - Septiana Roihanatus Sholihah; Kamiliatus Zahroh; Ahmad Shiddiq (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
Dyscalculia is a specific learning disorder that affects students' ability to understand basic math concepts. Handling this condition requires the active role of the teacher as the main facilitator in the learning process. This study aims to describe in depth the role of teachers in handling students with dyscalculia at SLB Yasmin Sumenep, and highlight the importance of coordination patterns between teachers and parents in supporting students' learning success. Using a qualitative approach with a case study method, data was obtained through observation and in-depth interviews with teachers. The results show that teachers not only function as teachers, but also as motivators and emotional companions for students. Teachers apply concrete and fun learning strategies, and create a supportive classroom atmosphere. In addition, the communication pattern between teachers and parents through a special group is an important factor in monitoring children's development and developing appropriate learning solutions. So, the role of adaptive, collaborative and empathic teachers determines the effectiveness of mathematics learning for students with dyscalculia. This study emphasizes the importance of continuous teacher training and strengthening the synergy between school and family to realize inclusive education.